2020
DOI: 10.3390/molecules25102363
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Application of Bio-Stimulants Enhancing the Production and the Toxicity of Origanum majorana Essential Oils Against Four Rice Seed-Borne Fungi

Abstract: In the present study, the enhancement of the production of Origanum majorana essential oils (EOs) was studied by treating plants with ascorbic acid (AA) and tryptophan (Trp) at concentrations of 100, 200 and 300 mg/L and Moringa oleifera leaf extract (MLE) at 2.5%, 5% and 10% as foliar applications during the seasons 2018–2019. The toxicities of the EOs were assayed against four seed-borne fungi (Bipolaris orzyae, Curvularia lunata, Fusarium verticilliodies and F. graminearum) isolated from rice grains (Oryzae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 52 publications
(54 reference statements)
0
30
0
Order By: Relevance
“…Fruit characteristics and yield were little, yet positively affected by the foliar application of CWE. It is evident that the foliar application of several types of extracts would exert a bio-stimulation effect on the growth and development of several plant species, for example, tomato [ 49 ], Origanum majorana [ 50 ], and geranium plants [ 51 ]. This might be attributed to the promoted biomass production as a result of enhancing the shoot and root fresh weights.…”
Section: Discussionmentioning
confidence: 99%
“…Fruit characteristics and yield were little, yet positively affected by the foliar application of CWE. It is evident that the foliar application of several types of extracts would exert a bio-stimulation effect on the growth and development of several plant species, for example, tomato [ 49 ], Origanum majorana [ 50 ], and geranium plants [ 51 ]. This might be attributed to the promoted biomass production as a result of enhancing the shoot and root fresh weights.…”
Section: Discussionmentioning
confidence: 99%
“…Perczak et al [ 41 ] reported that essential oils have great potential for inhibition of growth of Fusarium fungi on maize seeds. An O. majorana essential oil was shown to have antifungal activities against four seedborne fungi in rice: Fusarium verticilliodies , Fusarium graminearum , Bipolaris oryzae , and Curvularia lunata [ 42 ]. Van der Wolf et al [ 43 ] showed that thyme, oregano, cinnamon, and clove essential oils can reduce fungi on cabbage seeds, using the blotter method.…”
Section: Discussionmentioning
confidence: 99%
“…All the compounds were identified using their retention times and mass spectra by matching them with those from WILEY 09 and NIST 11 mass spectral databases. Standard Index and Reverse Standard Index measurements, with the Xcalibur 3.0 data system (3.0, Thermo Fisher Scientific Inc., Austin, TX, USA, 2014) of GC/MS, were used to confirm the identification of the compounds, where a value ≥650 is acceptable to confirm the compounds [ 6 , 7 , 15 , 16 , 17 , 18 , 19 , 20 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…Essential oils (EOs)—aromatic substances—can be obtained from different plant parts such as leaves, flowers, seeds, fruits, bark, wood, and roots by extraction using steam or hydrodistillation. Some plant EOs have recently been proven to be successful as ecofriendly biocontrol agents, with antibacterial, antifungal, antioxidant, insecticidal, and antiviral properties [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], and have potential uses as natural additives and wood-biofungicides [ 2 , 3 , 4 , 6 , 7 ] and in the food industry, [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%